NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI KENDUREI DULANG PAT - Nada Ismaya; Ratnawati Ratnawati; Dina Hajja Ristianti (Andragogi: Jurnal Pendidikan Islam dan Manajemen Pendidikan Islam, 2020)
This study aimed to investigate the portrayal of educational values contained in the Kendurei Dulang Pat tradition in Sukarame village, Rejang Lebong, Bengkulu, by using a qualitative approach. Data were collected using interviews, and then analyzed through some stages comprising reduction, data presentation, and drawing conclusion. This study revealed the following conclusion: Educational values in the Kendurei Dulang Pat tradition were  the value of I'tiqodiyah as shown that people believed that in the Kendurei Dulang Pat tradition, praying and whishing something were only resting upon Allah SWT; the value of amaliyah, in the implementation of Kendurei Dulang Pat, if prayer time came, prayer would be done first; and the value of khuluqiyah, in carrying out this tradition, mutual respects were shown wherein the elderly people sat at the front line and the youth sat at the back, and low attitudes were shown such as not boasting about one's health, instead always expecting everything only from Allah SWT and always making efforts to rest on Him.